PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Sari, Septia Puspita; Fathoni, Ahmad Fauzan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aims of this reseacrh is to examine the effect of Institusional Ownership, Size, Leverage and Dividend Policy on Firm Value. The sample of this reseach is taken from Property and Real Estate firms which are listed in Indonesia Stock Exchange during 2009 until 2012. Purposive sampling method is used to get the samples, and from 59 firms that we observed, we get 40 firm as the samples. To analyze the data Multiple Linier Regression, F- test, and t- test analysis with using SPSS 20. The result shows that all variables simultaneously and significanly affected toward firm value. However, t- test analysis indicates that only leverage that has significant effect on firm value.Keywords : Institusional Ownership, Size, Leverage, Dividend Policy and Firm Value